Optimalisasi Sumber Daya Tenaga Kerja Proyek Pembangunan Hotel Amaris Manado Dengan Metode Resource Leveling - Peginusa, Stefani Switly; Cyntha Tendean; Arnetha S. Raintung (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Construction projects inevitably encounter challenges related to time, labor, cost, and materials. If these issues aren't addressed promptly and effectively, new problems inevitably arise, such as delays in work duration, inefficient labor distribution, and delays in equipment and materials. The construction of the Amaris Hotel in Manado encountered significant challenges, particularly in structural work. A clear imbalance in labor allocation was identified, where the availability of labor in the field did not align with the project's needs. This discrepancy was exposed through unit price analysis of daily reports. This study aims to optimize human resources using the Resource Leveling method with Microsoft Project 2021 Software, addressing the ground floor structure to the roof floor. The results of the analysis showed that the duration of time required after the analysis did not change, namely 303 days. The study also determined the number of effective workers: 63 laborers, 34 builders, 3 foremen, and 3 building foremen.